PERANCANGAN BALAI PELATIHAN VOKASI DAN PRODUKTIVITAS DI BANJARBARU - Hatna Dewi; Ira Mentayani (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
The Vocational and Productivity Training Center is a transformation of the former Job Training Center, aimed at improving the quality and quantity of vocational training through competency-based programs, adequate learning facilities, and collaboration with business and industrial sectors. Banjarbaru City currently does not have a representative facility that functions as a central hub for skill development and local workforce productivity enhancement, indicating the need for a training center capable of responding to labor competency demands and increasing employment competitiveness. This project applies the principles of sustainable architecture through a Design Thinking approach, implemented in the planning of site massing, building design, and circulation systems to create an environmentally friendly, resource-efficient, and productive learning environment that harmonizes with nature. The proposed facility is expected to become a center for community empowerment, improvement of human resource quality, and support sustainable local economic growth.